Comparison between two different modes of non-invasive ventilatory support in preterm newborn infants with respiratory distress syndrome mild to moderate: preliminary data - F. Ciuffini; C. Pietrasanta; A. Lavizzari; S. Musumeci; C. Gualdi; S. Sortino; M. Colnaghi; F. Mosca (PAGEPress Publications, 2014)
Despite of improved survival of premature infants, the incidence of long term pulmonary complications, mostly associated with ventilation-induced lung injury, remains high. Non invasive ventilation (NIV) is able to reduce the adverse effects of mechanical ventilation. Although nasal continuous positive airway pressure (NCPAP) is an effective mode of NIV, traumatic nasal complications and intolerance of the nasal interface are common. Recently high flow nasal cannula (HFNC) is emerging as a better tolerated form of NIV, allowing better access to the baby's face, which may improve nursing, feeding and bonding. HFNC may be effective in the treatment of some neonatal respiratory conditions while being more user-friendly for care-givers than conventional NCPAP. Limited evidence is available to support the specific role, efficacy and safety of HFNC in newborns and to demonstrate efficacy compared with NCPAP; some studies suggest a potential role for HFNC in respiratory care of the neonate as a distinct non invasive ventilatory support. We present the preliminary data of a randomized clinical trial; the aim of this study was to assess efficacy and safety of HFNC compared to NCPAP in preterm newborns with mild to moderate respiratory distress syndrome (RDS).